I am reading Nielsen and Chuang on P. 291, for anyone interested in the origin of my question.
Given an annihilator a and its corresponding creator a_adj such that [a,a_adj] = 1 and another annihilator b with creator b_adj, I see that the argument in a proof claims the following:
Let G = a_adj*b - a*b_adj. Then,
[G,a ] = -b and [G,b] = a.
I don't see how these two relations hold. Can someone please point me in the right direction or prove them?
Thank you SOCommunity!
This post has been migrated from (A51.SE)